2012
DOI: 10.7882/az.2012.002
|View full text |Cite
|
Sign up to set email alerts
|

Disasters for wildlife: an analysis of media attention

Abstract: When disasters occur, media reporting tends to focus on the impacts on humans and their property, with only occasional references made to impacts on natural assets such as wildlife. We looked at a range of print and internet media sources to examine the way the media treat wildlife in their reporting of disasters. We found a growing media interest in wildlife problems from earlier analyses, at least partly generated by growing awareness of the risks to wildlife posed by global warming, a hot media topic. Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Overall, conservation-oriented media could be improved by journalists interacting more frequently with scientists (Rija and Kideghesho 2020). In a study of the media reporting of climate change impacts in Australia, Lunney and Moon (2012) noted that wildlife scientists should make more of an effort to connect with the media because they have a powerful role, and observed that policy makers respond to media interest. They also noted that wildlife conservation policy is often facilitated by the media, and thus scientists should be willing to connect more readily with the media.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, conservation-oriented media could be improved by journalists interacting more frequently with scientists (Rija and Kideghesho 2020). In a study of the media reporting of climate change impacts in Australia, Lunney and Moon (2012) noted that wildlife scientists should make more of an effort to connect with the media because they have a powerful role, and observed that policy makers respond to media interest. They also noted that wildlife conservation policy is often facilitated by the media, and thus scientists should be willing to connect more readily with the media.…”
Section: Discussionmentioning
confidence: 99%
“…This group is a common subject of study due to abundance, geographical range, attractiveness and charisma (Brooke et al, 2014). All this attention is also important to help increasing popular awareness, and even to raise funds for conservation (Lunney and Moon, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Malaysia, there is little use of communication in the form of media such as TV commercials, to educate the public about the effects of deforestation and promote acts of conservation. While in countries such as Australia, media coverage about wildlife conservation and threats to wildlife habitat loss is one of the highly reported issues (Lunney & Moon, 2012). This suggests that there are differences in terms of awareness of conservation issues as well as media attention between countries, particularly between developing and developed countries.…”
Section: Awareness Of Nature and Wildlife Conservation Issuesmentioning
confidence: 99%